Regionalizing culture : the political economy of Japanese popular culture in Asia - Otmazgin, Nissim (University of Hawaiʻi Press, 2014)
This book provides an empirically-grounded study of the production, circulation, and reception of Japanese popular culture in Asia. While many studies typically employ an interactive approach that focuses on the "meaning" of popular culture from an anthropological or cultural studies point of view, this book emphasizes that the consumption side and contextual meaning of popular culture are not the only salient factors in accounting for its proliferation. The production side and organizational aspects are also important. In addition to presenting individual case studies, the book offers a big-picture view of the dramatic changes that have taken place in popular culture production and circulation in Asia over the past two decades. The author has gleaned information from primary sources in Japanese, English, and other languages; research visits to Japan, Hong Kong, Singapore, Shanghai, Bangkok, and Seoul; as well as insights of people with firsthand knowledge from within the cultural industries. From this broad range of sources, he develops an integrative political economic approach to popular culture. This book offers a dialectical look at the organization of cultural production, primarily at the structure and control of cultural industries, interconnections between companies and production networks, and relations between the business sector and the state. It traces the rise of Japan as a popular culture powerhouse and the expansion of its cultural industries into Asian markets. It looks as well at the creation of markets for Japanese cultural commodities since the late 1980s, the industrial and normative impact that Japanese cultural industries have on the structure of the local cultural industries, and the wider implications these processes have for the Asian region. The growing popularity and importance of Japan's popular culture will make this book a basic text for scholars and students of popular culture as well as for those interested in political economy, media and communication studies, Japanese-Asian relations, Asian studies, and international relations. --